Assessment of biofuels production in Colombia. Issue 1 (1st January 2020) - Colmenares-Quintero, Ramón Fernando; Rico-Cruz, Camilo José; Stansfield, Kim E.; Colmenares-Quintero, Juan Carlos
Abstract: Different efforts have been carried out in the last years in order to find some alternatives for fossil fuels. Biofuels have been considered as one of the possible substitutes for fossil fuels because the majority of vehicles and co-generation systems can use them without any modification and produce fewer emissions. Additionally, some developing countries are presented as a good location for biofuels production due to their weather, economic and social conditions. The methodology used in this study is as follows: firstly, the current drivers and barriers that affect the production of biofuels in Colombia were identified in the available literature. The results showed Colombia presents some special conditions for the production of biofuels that allow it to generate a competitive advantage compared to other countries. However, some barriers can affect the adoption and production of biofuels in the country. Secondly, a survey was realised to biofuel producers, suppliers and researchers in order to validate their motivations and perceptions. Some similitudes and differences with regard to the literature were found in the surveys. Hence, this information allowed the authors to understand the reality of biofuels in Colombia from the views of the stakeholders. Additionally, a set of policies were analysed. The authors believe that this set of policies will help stakeholders to have a better production of biofuels in Colombia.